Impulse buying behaviour in tourism: A new perspective. (September 2021) - Karl, Marion; Chien, P. Monica; Ong, Faith
Highlights: Past research on impulse buying in tourism is fragmented and focuses on retail. Impulse buying can be premeditated and occur along the travel planning trajectory. Intertemporal decision-making provides a useful framework to study tourist impulse. Affective anticipation and self-regulation are potential mechanisms. Varied methods can be used to examine the impulse buying-travel decision nexus.